2016
DOI: 10.1038/srep19072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, Outcomes and Molecular Profiles of Drug Resistance in Tuberculous Meningitis in non-HIV Patients

Abstract: Tuberculous meningitis continues to be a serious problem for physicians because it is difficult to make an early diagnosis and the consequences of delaying treatment are severe. The objective of this study is to provide data for the optimization of diagnostic and timely treatment of tuberculous meningitis. Of the 401 human immunodeficiency virus (HIV)-negative tuberculous meningitis patients in our study, 332 were found to have an impaired blood brain barrier (82.8%). Nearly 17.0% of patients failed to be time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
13
0
2
Order By: Relevance
“…A recent study in Shenzhen, China indicated that, from 2006 to 2012, the proportion of CRF07_BC infections rapidly increased from 12.5% to 43.2%, whereas CRF01_AE and HIV‐1 B infections gradually decreased from 50.0% and 37.5% to 32.3% and 5.7%, respectively. In addition, the percentage of CRF55_01B rapidly increased from 0 in 2006 to 16.0% in 2012 . These results highlight the need to evaluate the natural history and progression of HIV‐1 infection caused by different HIV‐1 genotypes, in particular the two major CRF01_AE and CRF07_BC variants as well as CRF55_01B, which has newly emerged but is rapidly increasing in China.…”
Section: Introductionmentioning
confidence: 95%
“…A recent study in Shenzhen, China indicated that, from 2006 to 2012, the proportion of CRF07_BC infections rapidly increased from 12.5% to 43.2%, whereas CRF01_AE and HIV‐1 B infections gradually decreased from 50.0% and 37.5% to 32.3% and 5.7%, respectively. In addition, the percentage of CRF55_01B rapidly increased from 0 in 2006 to 16.0% in 2012 . These results highlight the need to evaluate the natural history and progression of HIV‐1 infection caused by different HIV‐1 genotypes, in particular the two major CRF01_AE and CRF07_BC variants as well as CRF55_01B, which has newly emerged but is rapidly increasing in China.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous studies have been reported on various other parameters as biomarkers in CSF for the diagnosis of TBM, including a predominance of lymphocytes, decreased glucose level and increased protein level [ 22 ]. Elevated CSF adenosine deaminase (ADA) activity has been observed in TBM patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nearly 24.9% of the patients exhibited signs of meningeal irritation in children especially under 3 years of age. The prevalence of all other symptoms and signs were less than 20% [ 39 ]. On the other side, bacterial meningitis is present in 30% of children with signs of meningeal irritation.…”
Section: Methodsmentioning
confidence: 99%